Dung Analysis and its Correlation with Three Different Species of Extinct Megafauna in the Southern Argentinian Puna - Martinez, Jorge Gabriel (2010)
This paper presents the results and implications of the analysis of various samples of dung assigned to extinct Pleistocene megafauna in the Southern Argentinian Puna (ca. 19,600–12,500 RCYBP) (Martínez et al. 2004, 2007). Although there are several works related to the study of coprolites of extinct Pleistocene megafauna in the Americas (Poinar et al. 1998, Steadman et al. 2005, Kropf et al. 2007, among others), only a few deal with morphological aspects.